Genetic Architecture of Primary Tauopathies. (10th May 2023) - Gallo, Daniel; Ruiz, Agustín; Sánchez-Juan, Pascual
Highlights: The most relevant genetic risk factor for primary Tauopathies is MAPT H1c haplotype . Outside of MAPT, several other genes have been robustly associated with PSP. There is a high degree of genetic overlap across the different primary Tauopathies. Abstract: Primary Tauopathies are a group of diseases defined by the accumulation of Tau, in which the alteration of this protein is the primary driver of the neurodegenerative process. In addition to the classical syndromes (Pick's disease (PiD), progressive supranuclear palsy (PSP), corticobasal degeneration (CBD), and argyrophilic grain disease (AGD)), new entities, like primary age-related Tauopathy (PART), have been recently described. Except for the classical Richardson's syndrome phenotype in PSP, the correlation between the clinical picture of the primary Tauopathies and underlying pathology is poor. This fact has challenged genetic studies. However, thanks to multicenter collaborations, several genome-wide association studies are helping us unravel the genetic structure of these diseases. The most relevant risk factor revealed by these studies is the Tau gene ( MAPT), which, in addition to mutations causing rare familial forms, plays a fundamental role in sporadic cases of PSP and CBD in which there is a strong predominance of the H1 and H1c haplotypes. But outside of MAPT, several other genes have been robustly associated with PSP. These findings, pointing towards multifactorial causation, imply the participation of several pathways involving the myelin sheath integrity, the endoplasmic reticulum unfolded protein response, microglia, intracellular vesicle trafficking, or the ubiquitin–proteasome system. Additionally, GWAS show a high degree of genetic overlap across different Tauopathies. This is especially salient between PSP and CBD, but also GWAS studying the recently described PART phenotype shows genetic overlap with genes that promote Tau pathology and with others associated with Alzheimer's disease.